Pelatihan Pembuatan Media Pembelajaran Interaktif Menggunakan Canva Melalui Metode Service Learning Guru-Guru Sekolah Dasar - Desak Made Darmawati; Nur Busyra; Jamil Latief; Muhammad Alimudin (TAAWUN, 2024)
The training on creating interactive learning media using Canva through the service learning method was conducted to enhance the teaching competencies of elementary school teachers in the era of Industry 4.0. This Community Service Program (PKM) aimed to increase teachers' knowledge and understanding of developing e-learning-based learning media. The activity was held at SD Muhammadiyah 11, Bidaracina Village, East Jakarta, on May 22, 2024, from 8:00 AM to 12:00 PM, with ten teachers participating. The training included a pretest, mentoring, and a posttest conducted by the FKIP UHAMKA lecturer team. The results showed an improvement in teachers' knowledge of the steps in creating Canva-based learning media, the creation of e-learning-based teaching materials, and positive responses from the participants. Teachers demonstrated the ability to create and effectively use e-learning-based learning media. This training successfully enhanced the teachers' competencies in using Canva as an interactive learning media.